ANALISIS PENGARUH KEPUASAN, TRANSPARANSI DAN AKUNTABILITAS TERHADAP LOYALITAS MEMBAYAR INFAQ DAN SEDEKAH (Studi Pada Lembaga Pengelola Zakat “PAY&DoIT” Kota Jakarta) - Nugraha, Alvin (Islamic Economics and finance in Focus, 2023)
The potential for ziswaf in Indonesia continues to increase every year, but the amount of ziswaf collected is insignificant compared to the potential for ziswaf which reaches 327.6 trillion rupiahs. As non-profit organizations, zakat management institutions need to pay attention to several variables so that donors are willing to spend part of their wealth, and this will create donor loyalty. This study uses satisfaction, transparency, and accountability variables to determine whether these variables affect donor loyalty. In this study, data were collected through questionnaires with purposive sampling. Respondents in this study amounted to 50 respondents who donated their wealth through the zakat management institution "PAY&DoIT" for 2x or more in the last 6 months. The analysis technique used is multiple linear regression analysis. The results of this study indicate that the variables of satisfaction and transparency have a positive and significant influence on donor loyalty. Meanwhile, the accountability variable has a positive but not significant effect on donor loyalty